Value determinants of plant extractivism in Brazil - Sven Wunder (Institute for Applied Economic Research (ipea), 2015)
This study analyses the structure and development trends for plant extraction in Brazil. It is a sub-sector of agriculture that has received considerable international attention, due to its alleged potentials for promoting the sustainable use of tropical forests and other natural ecosystems, e.g. through the harvesting of non-wood products in extractive reserves. The main data source is the latest Agricultural Census (1995/96) from IBGE, the Brazilian Statistical Office - a source that possesses both strengths and weaknesses. Extraction in all of Brazil is described generally; for the Legal Amazon, causes of spatial value differences are explained econometrically. It is found that extraction exhibits a long-run structural decline vis-à-vis agricultural cultivation, which accelerates during the last decade. Nonwood values, a minor element within that sector, occur extremely concentrated on a few products and market-near geographical areas with special ecological characteristics, that are little representative for tropical forests in a wider sense. It is concluded that the favourable outlook on non-wood extraction, promoted by other scholars' previous, site-specific case studies, may be over-optimistic if applied to a more general setting.
Keywords: 330